Diversification of livelihoods among small-scale farmers in the Nyando Basin, Kenya: Findings from a climate-smart agriculture baseline survey - Mumo, Elijah (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
This brief summarizes findings of a climate-smart agriculture (CSA) research project led by the Amsterdam Center for World Food Studies (ACWFS) with the participation of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) in East Africa, University of Nairobi (School of Economics) and Wageningen Economic Research. It is based on baseline data collected as part of an ongoing survey of 122 households located in the Climate-Smart Villages (CSVs) and non-CSVs villages of Nyando Basin in Kisumu and Kericho Counties. It discusses diversification of livelihood sources.